Evaluation of peripheral blood NK cell subsets and cytokines in unexplained recurrent miscarriage. Issue 12 (December 2018) - Rad, Hajar Adib; Basirat, Zahra; Mostafazadeh, Amrollah; Faramarzi, Mahbobeh; Bijani, Ali; Nouri, Hamid Reza; Amiri, Shima Soleimani
Abstract : Background: : Recurrent miscarriage is considered as one of the main problems in women's reproductive health. The aim of the present study was to evaluate the natural killer cells (NK cells) and cytokines in unexplained recurrent miscarriage and fertile women. Methods: : In this case–control study, 40 women with unexplained recurrent miscarriage were assigned to the case group and 40 fertile women were assigned to the control group. NK cell subsets (CD56 + CD16 + /CD56 + CD16 ‐ ) and cytokines (IL‐2/IL‐12) levels in the peripheral blood (PB) were used for assessing immunologic problems. The percentage of peripheral blood NK cells (CD56 dim/bright ) was identified by flow cytometry. Results: : The obtained results showed a significant difference in CD56 + CD16 + and CD56 + CD16 ‐ between the two groups. Also, there was no significant difference in the IL‐2 and IL‐12 between the two groups. A cut‐off value of ≥5.25% ( p < 0.001) and ≥3.4% ( p < 0.015) for the increased percentage of CD56 + CD16 + and CD56 + CD16 − cells in the PB become predictive of recurrent miscarriage. Conclusion: : Increased NK cells in the PB of women with recurrent miscarriage strongly establish prospective researches to recognize the predictive value of these parameters in the evaluation of patients with recurrent miscarriage.